Comparison of abdominal computed tomography to ultrasonography in the diagnosis of biliary disease in dogs with acute abdominal signs - Marroquin, Shanna M.; Lee, Alison M.; Seitz, Marc A.; Wills, Robert W.; Woodruff, Kimberly Ann (Frontiers in Veterinary Science, 2025)
IntroductionComputed tomography (CT) is becoming increasingly popular for canine patients; however, limited information is available comparing its performance to ultrasonography (US) in identifying canine biliary pathology causing acute abdominal signs. The purpose of this study was to compare the diagnostic performance of CT and US in detecting canine biliary disease. We hypothesized that CT would detect various canine biliary diseases with similar accuracy comparable to US, while US would be superior to CT in evaluating the bile ducts and diagnosing cholecystitis due to the small size of these structures.MethodsIn this prospective, observational study, 35 client-owned dogs presenting with acute abdominal signs and suspected biliary disease—based on physical examination, complete blood count, and serum chemistry—underwent both abdominal US and arterial and venous phase abdominal CT. Two authors reviewed the randomized, anonymized CT and US studies to measure biliary structures and evaluate for biliary pathology. Agreement between each imaging modality and the final clinical diagnoses for biliary pathology was assessed by intraclass correlation coefficients (ICCs).ResultsTwenty-eight dogs had biliary pathology, and seven dogs served as controls with no evidence of biliary disease. There were variable degrees of good to perfect agreement between US and CT to identify gallbladder mucoceles, gallbladder wall mass, and cholecystitis, moderate agreement when comparing gallbladder wall thickness, and poor agreement to identify cholelithiasis.ConclusionThe findings from this study suggest that CT may be used in place of US in canine patients presenting for acute abdominal signs with concern for biliary in origin.